2015
DOI: 10.1186/s12885-015-1204-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment neutrophil to lymphocyte ratio may be a useful tool in predicting survival in early triple negative breast cancer patients

Abstract: BackgroundThere is a growing body of evidence that immune response plays a large role in cancer outcome. The neutrophil to lymphocyte ratio (NLR) has been used as a simple parameter of systemic inflammation in several tumors. The purpose was to investigate the association between pre-treatment NLR, disease-free survival and overall survival in patients with early triple negative breast cancer (TNBC).MethodsWe reviewed the records of patients with stage I-III TNBC at our Institution from 2006 to 2012. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 49 publications
10
88
3
2
Order By: Relevance
“…Multiple studies have confirmed that NLR is an easily available and reliable marker, which is associated with poor prognosis in various malignancies (19)(20)(21)(22)(23). The present study revealed that NLR was significantly associated with TNM stage, tumor invasion, tumor size, distant metastasis and poor prognosis, which was consistent with a previous study (43).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Multiple studies have confirmed that NLR is an easily available and reliable marker, which is associated with poor prognosis in various malignancies (19)(20)(21)(22)(23). The present study revealed that NLR was significantly associated with TNM stage, tumor invasion, tumor size, distant metastasis and poor prognosis, which was consistent with a previous study (43).…”
Section: Discussionsupporting
confidence: 91%
“…NLR represents the balance between inflammatory activation and regulatory factors (19). Increased NLR may also serve as an independent prognostic risk factor in multiple types of cancer, including lung (20) and breast cancer (21), renal cell carcinoma (22), and ovarian cancer (23 Statistical analysis. Data are expressed as the mean ± standard deviation.…”
Section: Introductionmentioning
confidence: 99%
“…44 In a recently published Italian trial, in which the significance of NLR was explored in 90 triple negative patients with breast cancer by means of ROC analysis, NLR >3 was associated with worse survival. 45 Finally, in two cohorts of 363 and 147 patients, respectively, treated with conservative breast surgery (and intraoperative non-steroidal antiinflammatory drugs) at Louvain University, disease-free survival and overall survival were shown to be significantly correlated with high NLR (>3.3), as calculated by ROC analysis. 46 It should be noted that the NLR cut-off value selected by ROC curve analysis in our study (1.97) is lower than that used in the abovementioned papers.…”
Section: Discussionmentioning
confidence: 95%
“…In those studies, a high nlr was associated with poor survival probability. In breast cancer, the role of the nlr as a prognosticator has been evaluated in various settings 17,19,32,33 . Azab et al 17 were the first to report that the nlr is an independent predictor for both short-and long-term mortality, with a higher nlr being associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%